Median nerve ultrasonography in carpal tunnel syndrome - Ehler, Edvard (My University, 2018)
Carpal tunnel syndrom is the most common mononeuropathy. The pathology relates to compression, entrapment or irritation of the median nerve within the carpal tunnel. The diagnosis may be a clinical one supported by electrophysiological findings. Ultrasonography in patients with carpal tunnel syndrome is increasingly used. Ultrasonography in patients with electrophysiologically confirmed carpal tunnel syndrome has the advantage of not only confirming structural changes characterizing the compressed median nerve, but also to find another pathology not diagnosed byl electrophysiology.
Ultrasonografie středního nervu u syndromu karpálního tunelu
Keywords: carpal tunnel syndrome; electophysiology; ultrasonography; structural findings; syndrom karpálního tunelu; elektrofyziologie; ultrasonografie; strukturální změny